Analisis Program Undangan Khodim Al-Haromain Al-Syarifain mengenai Pelaksanaan Ibadah Haji dan Umrah - Wahyudin, Yuyu; Hendra, Testru; Abdullah, Mawardi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2024)
Hajj is the fifth pillar of Islam, the law is obligatory for a Muslim who already has the ability; physical, financial and other things. The enthusiasm of the Indonesian Muslim community for the Hajj pilgrimage is very high, as evidenced by the very long waiting list, 32 years. ‘The Program for the Guests of the Custodian of the Two Holy Mosques for Hajj and Umrah’ is one solution for some Muslims in Indonesia and even the world to realize their dreams. With this research, it is hoped that Muslims will get the correct information about ‘’The Program for the Guests of the Custodian of the Two Holy Mosques for Hajj and Umrah’. So that Muslims who experience financial limitations remain enthusiastic because they can perform Hajj through this Program. This research uses qualitative research methods, with a case study approach. The Government of the Kingdom of Saudi Arabia (KSA) has facilitated and made it easy for Muslims in Indonesia and the world to realize their holy intentions; To perform the Hajj pilgrimage for free, without having to queue, with five-star hotel facilities and other excellent facilities. The government of the Kingdom of Saudi Arabia (KSA) since 1417H/1996M every year invites thousands of Muslims -from all over the world- who are considered to have contributed to Islam and the Muslims to perform the Hajj and Umrah for free through the Program. Every Muslim who wants to become a participant in this program can submit their application to the Saudi Arabian Embassy.